2016
DOI: 10.1073/pnas.1521269113
|View full text |Cite
|
Sign up to set email alerts
|

Neandertals revised

Abstract: The last decade has seen a significant growth of our knowledge of the Neandertals, a population of Pleistocene hunter-gatherers who lived in (western) Eurasia between ∼400,000 and 40,000 y ago. Starting from a source population deep in the Middle Pleistocene, the hundreds of thousands of years of relative separation between African and Eurasian groups led to the emergence of different phenotypes in Late Pleistocene Europe and Africa. Both recently obtained genetic evidence and archeological data show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 112 publications
1
55
0
Order By: Relevance
“…Neanderthals once covered a vast and climatically and ecologically diverse range, from Siberia to Gibraltar, and contrary to earlier stereotypes, they did adapt their diet and technology to local conditions [13,44]. In northern latitudes, they were predominantly carnivorous, had advanced leather processing technology (using lissoirs, probably later borrowed by AMH [45]), with modeling studies suggesting advanced winter clothing [46] using stone and bone awls (such as found in the Grotte du Renne) as sewing aids [47], but in general their diet was apparently very flexible and adapted to the local environment, including both meat and vegetable foods [48] to varying proportions [13,[49][50][51].…”
Section: Neanderthal Cognition As Evidenced By Archeologymentioning
confidence: 97%
“…Neanderthals once covered a vast and climatically and ecologically diverse range, from Siberia to Gibraltar, and contrary to earlier stereotypes, they did adapt their diet and technology to local conditions [13,44]. In northern latitudes, they were predominantly carnivorous, had advanced leather processing technology (using lissoirs, probably later borrowed by AMH [45]), with modeling studies suggesting advanced winter clothing [46] using stone and bone awls (such as found in the Grotte du Renne) as sewing aids [47], but in general their diet was apparently very flexible and adapted to the local environment, including both meat and vegetable foods [48] to varying proportions [13,[49][50][51].…”
Section: Neanderthal Cognition As Evidenced By Archeologymentioning
confidence: 97%
“…With Levallois technology, specialized lithic points (and other flake variants such as radial and laminar flakes) can be made for hafting and the creation of stone‐tipped spears. In addition, we have good evidence for the Neanderthal creation and use of pitch as a binding agent in composite tool production (Wragg Sykes et al, ; Roebroeks and Soressi, ). Using composite tools, certain cognitive thresholds must have been crossed by the creating species (Barham, ).…”
Section: Updating Neanderthal Behaviourmentioning
confidence: 99%
“…This situation is paralleled outside of Africa, where most of the manufacturing techniques that characterize the MSA were also mastered by Neanderthals and possibly by Denisovans (Roebroeks and Soressi, 2016d’Errico and Banks, 2013 ). These archaic populations diverged from African populations well before the appearance of such techniques either in Africa or in Eurasia (Meyer et al, 2016), so these techniques must either have been invented independently multiple times or have been transferred by long-distance exchange of ideas across long-separated hominin populations.…”
Section: Introductionmentioning
confidence: 98%